The Moderating Effect of Computational Thinking and Multirepresentation on the Relationship of Academic Resilience and Biology Literacy in Indonesian High School Students - Fatmawati, Any; Jamaluddin, Asham Bin; Mursali, Saidil; Dewi, Ika Nurani (FKIP Universitas Lampung, 2025)
Academic resilience helps students overcome learning challenges and stay motivated in understanding complex biology materials. Computational thinking skills enable students to break down complex biology problems logically and structured, while the use of multirepresentations such as diagrams and graphs facilitates the understanding of abstract concepts. Biological literacy has a very important urgency for students because it plays a role in equipping them with the ability to understand, analyze, and apply biological concepts in everyday life. In the era of globalization and rapid development of science, biological literacy is an important basis for making intelligent decisions, especially related to environmental, health, and sustainability issues. The objective of this study is to investigate the influence of academic resilience on the biological literacy of students by means of computational thinking and multirepresentations. It is hypothesized that students' capacity to surmount intricate biology learning obstacles is enhanced by their high academic resilience. This study examines the correlation between academic resilience, computational thinking, multirepresentations, and biological literacy in high school pupils in Mataram City, Indonesia, utilizing quantitative methods and Structural Equation Modeling (SEM) analysis. The findings indicated that academic resilience has a substantial impact on the biological literacy of students (p < 0.05), both directly and through the mediation of computational thinking abilities and the use of multirepresentations. Computational thinking assists students in the deconstruction of intricate biological problems, while multirepresentations, such as diagrams and graphs, facilitate comprehension of abstract biological concepts. This study underscores the significance of fostering academic resilience, computational thinking, and visual representations in order to enhance students' biological literacy, thereby facilitating the development of more effective and adaptive biology learning strategies. Keywords: academic resilience, biology literacy, computational thinking, multirepresentation, students.